Pilgrimage Tourism and Domestic Tourism in Uzbekistan Principles of Development - Shodieva Gulnoza Nematilloevna (International Journal on Integrated Education, 2023)
The article describes the development of pilgrimage tourism in the country, the function and importance of domestic tourism and their development, and ways to successfully use traveler assets in the regions.